'Out of sight, out of mind?' A follow-up on HIV-infected patients with drug-resistant pulmonary tuberculosis in Uganda: A case series. (June 2021) - Notarfrancesco, Marco; Castelnuovo, Barbara; Kaelin, Marisa; Fehr, Jan; Sekaggya-Wiltshire, Christine
Among new tuberculosis cases in Uganda, 10.3% are drug-resistant and 43% occur in people living with HIV. Both resistance and HIV–tuberculosis co-infection lead to unfavourable tuberculosis treatment outcomes. In this case series, we followed up eight HIV–tuberculosis co-infected patients withdrawn from a pharmacokinetics study on anti-tuberculosis drugs between April 2013 and April 2015 following a diagnosis of drug-resistant tuberculosis. We identified resistance patterns and treatment regimens and evaluated their tuberculosis treatment outcomes. Two patients were multidrug-resistant, only one out of eight was treated according to the World Health Organization guidelines applicable at that time and five had unfavourable tuberculosis treatment outcomes, that is, were lost to follow-up, could not be evaluated or died. Taken together, we found unfavourable tuberculosis treatment outcomes for patients with drug-resistant tuberculosis. This indicates the necessity of implementation of current treatment guidelines and close monitoring for patients with drug-resistant tuberculosis.